Fisiologia do crescimento e desenvolvimento de frutos e sementes de Phaseolus vulgaris L., - Ayres, Samara Dayse da Luz (2018)
The Phaseolus vulgaris species important worldwide, it can be consumed in the form of beans or pods. The aim of this study was to evaluate the physiological growth and development of the fruits, seeds and seedlings of the Snap bean cultivars 'Macarrão Trepador' and 'Rasteiro Fartura'. The field experiment was carried out in the Olericultura module at the Olho d'Água belonging to the Campus II of the UFPB, Areia - Paraíba, Brazil. The harvesting began five days after the opening of 50% of the flowers, with intervals of every five days, totaling seven harvestings. The fruits were sent to the The Laboratório de Análise de Sementes of the Centro de Ciências Agrárias, UFPB, Areia-PB. The experimental design used in the laboratory was a completely randomized design (CRD). For seed germination and fruit analysis, the samples were taken from the third harvesting. The following variables were evaluated: Weight of one hundred seeds, first germination counting, germination, average time for germination, length and root and shoot dry matter, crude protein, neutral detergent fiber, acid detergent fiber and lignin. The physiological maturity was verified at 35 DAA (Days after anthesis) for the cultivar 'Macarrão Trepador and 37 DAA for 'Rasteiro Fartura', a period in which the seeds are with the maximum dry matter and the minimum water content. The chemical composition of both cultivars is similar, with the exception of lignin-like, which presented at 25 DAA for the 'Rasteiro Fartura' cultivar higher values compared to the cultivar „Macarrão Trepador‟. The seed dry matter, first germination counting, germination and, average time for germination were efficient to determine the physiological maturity of the seeds.